How to the regional financial management in Bengkalis Regency? - Sonia Efriani; Nur Azlina; Mudrika Alamsyah (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2020)
Regional financial management is all rights and obligations in the context of running a regional government that can be valued in money, including all forms of wealth related to the rights and obligations of the region and of course within the boundaries of regional authority. This study aims to examine the effect of financial accountability, supervision, budget transparency and financial report presentation on local government financial management. Population and sample in this study amounted to 32 SKPD and 96 respondents. The sampling method used in this research is positive sampling, namely the sampling technique with certain considerations. The data used in this study are primary data. The data collection technique used survey techniques, namely by distributing questionnaires. The analysis used in this study is multiple regression analysis, f test and t test.